Inducing α″ phase by interstitial carbon atoms to achieve strength-ductility enhancement in as-printed Ti alloy - Xuemeng Gan; Dong Ye; Shaofu Li; Shunyuan Xiao; Chaoquan Hu; Katsuyoshi Kondoh; Shota Kariya; Lei Zhang; Yafeng Yang (Materials Research Letters)
Intermediate α″ phase was constructed in as-printed Ti alloys by introducing interstitial carbon atoms to mitigate the detrimental effects of α′ martensite on ductility. The interstitials served as a lattice modulation limiter to achieve an incomplete atomic shuffle during martensitic transformation process to form metastable α″ phase, followed by stabilizing the α″ to inhibit the growth of α′ martensite. The resulting microstructure, characterized by a dominant α/α′ matrix decorated with fine α″ phase, enhanced twinning formation ability and induced dynamic Hall–Petch and grain refinement strengthening effects. This resulted in simultaneous improvements in both strength and ductility.